Hallux Limitus Influence on Plantar Pressure Variations during the Gait Cycle: A Case-Control Study - Claudia Cuevas-Martínez; Ricardo Becerro-de-Bengoa-Vallejo; Marta Elena Losa-Iglesias; Israel Casado-Hernández; Emmanuel Navarro-Flores; Laura Pérez-Palma; João Martiniano; Juan Gómez-Salgado; Daniel López-López (Bioengineering, 2023)
Background: Hallux limitus is a common foot disorder whose incidence has increased in the school-age population. Hallux limitus is characterized by musculoskeletal alteration that involves the metatarsophalangeal joint causing structural disorders in different anatomical areas of the locomotor system, affecting gait patterns. The aim of this study was to analyze dynamic plantar pressures in a school-aged population both with functional hallux and without. Methods: A full sample of 100 subjects (50 male and 50 female) 7 to 12 years old was included. The subjects were identified in two groups: the case group (50 subjects characterized as having hallux limitus, 22 male and 28 female) and control group (50 subjects characterized as not having hallux limitus, 28 male and 22 female). Measurements were obtained while subjects walked barefoot in a relaxed manner along a baropodometric platform. The hallux limitus test was realized in a seated position to sort subjects out into an established study group. The variables checked in the research were the surface area supported by each lower limb, the maximum peak pressure of each lower limb, the maximum mean pressure of each lower limb, the body weight on the hallux of each foot, the body weight on the first metatarsal head of each foot, the body weight at the second metatarsal head of each foot, the body weight at the third and fourth metatarsal head of each foot, the body weight at the head of the fifth metatarsal of each foot, the body weight at the midfoot of each foot, and the body weight at the heel of each foot. Results: Non-significant results were obtained in the variable of pressure peaks between both study groups; the highest pressures were found in the hallux with a p-value of 0.127 and in the first metatarsal head with a p-value 0.354 in subjects with hallux limitus. A non-significant result with a p-value of 0.156 was obtained at the second metatarsal head in healthy subjects. However, significant results were observed for third and fourth metatarsal head pressure in healthy subjects with a p-value of 0.031 and regarding rearfoot pressure in subjects with functional hallux limitus with a p-value of 0.023. Conclusions: School-age subjects with hallux limitus during gait exhibit more average peak plantar pressure in the heel and less peak average plantar pressure in the third and fourth metatarsal head as compared to healthy children aged between 7 and 12 years old.